ANALISIS USAHATANI KAKAO RAKYAT DI KABUPATEN SOLOK SUMATERA BARAT - Buharman B (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACT Analysis of Cocoa Small-Farming in Solok District, West Sumatera Province. Solok District is one of the districts that promote the development of cacao plantation in West Sumatera. The development of cacao plantation is physically conducive, however economically is questionable because the existence of other competitive commodities. The objective of the assessment was to analyze the farming systems feasibility as the basis for further development of cacao plantation in West Sumatera. A survey was conducted with 30 farmer’s respondents by purposive method in Solok District West Sumatra 2012. The data collection consisted of quantity and value of input-output of cacao farming and cost and revenue components. Data was analyzed using the criteria of financially feasible infestation with parameters Benefit Cost Ratio (B/C); Net Present Value (NPV); internal Rate of Return (IRR) and Pay Back Period (PBP). The financial analysis gather in 20 year, at discount factor (DF) 12% indicated the  B/C 1.649; NPV IDR37,889,134;  IRR 30.16%; and PBP at year 5th to 6th. The results from sensitivity analysis, with the cost of production increased by 25%, and the benefit increased by 10% cocoa farming was financially feasible, that shown by the indicator of B/C value for 1.452; NPV IDR32,930,170; IRR 26.10% which was more than the rate  for commercial level. To improve the competitive of cacao in West Sumatera, there is a need the application of good farming practice which includes the use of high yield varieties, integrated pest and disease protection, fertilizer, and topping technologies. In addition, the efforts should be followed by the improvement of skill and knowledge of farmers involved in cacao farming.Keywords: Cacao, cultural practices, financial analysisABSTRAK Kabupaten Solok merupakan salah satu daerah penghasil kakao di Sumatera Barat. Secara fisik perkembangan kakao di Sumatera Barat menunjukkan keragaan yang relatif baik, namun dari sisi ekonomi masih dipertanyakan karena adanya komoditi alternatif yang menjadi pesaing. Kajian ini bertujuan untuk menganalisis kelayakan finansial usahatani kakao, sebagai dasar pertimbangan untuk pengembangan lebih lanjut di Sumatera Barat. Survai dilakukan terhadap 30 orang petani kakao yang ditentukan secara sengaja sebagai responden. Pengkajian dilakukan di Kabupaten Solok, Sumatera Barat tahun 2012. Data yang dikumpulkan mencakup komponen budidaya, kuantitas dan nilai masukan-hasil usahatani kakao, serta komponen biaya dan penerimaan. Analisis data menggunakan kriteria kelayakan investasi secara finansial, dengan parameter B/C; NPV; IRR dan PBP. Hasil analisis selama 20 tahun pada tingkat discound factor 12% menunjukkan bahwa investasi dinilai layak secara finansial yang ditunjukkan nilai B/C sebesar 1.649; NPV Rp37.889.133,72; IRR 30,16%; dan PBP jatuh pada tahun ke 5-6. Hasil analisis sensitivitas, dengan kenaikan biaya produksi 25% dan penerimaan naik 10% usahatani kakao secara finansial masih layak, ditunjukkan oleh indikator B/C 1,452; NPV Rp32.930.169,58; IRR 26,10% lebih besar dari suku bunga komersial (12%). Untuk meningkatkan daya saing kakao di Sumatera Barat diperlukan perbaikan teknologi budidaya yang tepat, meliputi penggunaan klon unggul, pengendalian hama terpadu (PHT), pemupukan, dan pemangkasan. Disamping itu, upaya tersebut perlu diikuti dengan peningkatan pengetahuan dan keterampilan petani sebagai pengelola usahatani kakao.Kata kunci: Kakao, keragaan budidaya, analisis finansial